Ecospirituality in Religious Education: Integrating Deep Ecology and Faith-Based Pedagogy to Promote Sustainable Living - Marudut Bernadtua Simanjuntak; Reza Noprial Lubis; Sergius Lay (Green Philosophy: International Journal of Religious Education and Philosophy, 2024)
As environmental challenges continue to intensify globally, there is an increasing need for educational systems to foster ecological awareness and sustainable living practices. This paper explores the integration of ecospirituality within religious education, combining deep ecology and faith-based pedagogy to promote environmental consciousness among students. Ecospirituality, a concept that merges ecological awareness with spiritual beliefs, provides a holistic framework that not only encourages ecological stewardship but also aligns these practices with religious values. The paper examines key principles of deep ecology, such as the interconnectedness of all life, biospherical egalitarianism, and anti-consumerism, and explores their application in educational contexts. It also delves into how religious education has historically approached environmental issues, particularly through faith-based pedagogies that emphasize moral responsibility for creation. Using a qualitative research approach, the study conducts content analysis of religious curricula, interviews with educators, and textual examination of religious literature to uncover ecological principles within religious teachings. The findings suggest that the integration of ecological themes into religious education enhances students' understanding of environmental ethics and strengthens their connection to nature. Despite challenges such as resistance to curriculum changes, variations in theological interpretations, and the need for teacher training, the study highlights innovative solutions, including professional development and curriculum adaptation. The comparison with secular environmental education models shows that ecospirituality offers a unique approach by embedding sustainability within spiritual practices. The paper concludes by recommending further research and curriculum development to ensure that ecospirituality can play a central role in shaping a sustainable future through education.